Risk Factors, Levels of Spirituality and Alcohol Use in Students of Two Nursing Courses - Pillon, Sandra Cristina; Santos, Manoel Antônio dos; Gonçalves, Angélica Martins de Souza; Araújo, Keila Maria de; Funai, Anderson (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2010)
The purpose of this cross-sectional study was to analyze the relationships existing between risk factors, levels of spirituality and alcohol use among students of two nursing courses. The sample consisted of 313 students. The following were used: questionnaire with sociodemographic information, Alcohol Use Disorder Identification Tests, and Spirituality Scale. Most participants were young females, single and catholic. Alcohol use was present in 83.4% of the sample and in nearly one third it was considered to be an alcohol use disorder. The risk factors were male gender and a low score on the spirituality levels. Studies of this nature are of great value in planning programs for the prevention of alcohol use in the university.